Contribuição da anatomia do lenho à taxonomia do gênero Mimosa L., com base em espécies do sul do Brasil - Machado, Paulo Fernando dos Santos (2020)
In order to investigate the contribution of wood anatomy to the taxonomy of Mimosa L., microtechnical work was carried out previously the microscopic description of nine wood species and, for a quantitative analysis, were aggregated thirteen other species (M. berroi, M. bimucronata, M. cruenta, M. daleoides, M. eriocarpa, M. flocculosa, M. incana, M. micropteris, M. pilulifera, M. scabrella, M. sparsa, M. trachycarpa, M. uraguensis), whose data were collected from the literature. The six species of the Stipellares series (M. barnebiana, M. bifurca, M. cruenta, M. intricata, M. trachycarpa, M. uraguensis) have been shown to constitute a taxonomically distinct group, by its homogeneous rays and pores in racemiform multiples, tending to a dendritic pattern. For the Calothamnos section (M. berroi, M. daleoides, M. eriocarpa, M. flocculosa, M. incana, M. pilulifera, M. scabrella, M. taimbensis) and Obstrigosae subseries (M. adpressa, M. parvipinna, M. ramulosa), despite the significant number of species investigated, no characters of recognized taxonomic value were found, being distinguished based on quantitative aspects. In the case of the series Bimucronatae (M. bimucronata), Habbasia (M. pigra), Myriophyllae (M. balduinii, M. micropteris) and the subseries Sparsae (M. sparsa), the small number of species investigated does not allow the recognition of distinctive taxonomic features. Finally, the gathering of primitive and evolved characters in the wood structure confirms the heterogeneity of Mimosa L. reported in the literature and recommends a basal position for this botanical genus in clado Mimosoideae and subfamily Caesalpinioideae.